Power-to-hydrogen pathway in the transport sector: How to assure the economic sustainability of solar powered refueling stations. (15th January 2022) - Silvestri, L.; Di Micco, S.; Forcina, A.; Minutillo, M.; Perna, A.
Highlights: An incentive strategy for the development of Hydrogen Refueling Stations is proposed. The incentive strategy concerns the money valorization of the avoided carbon dioxide. The hydrogen and gasoline pathways are compared by using the Well-To-Wheel analysis. The solar hydrogen pathway has a better carbon offprint compared to the gasoline one. High shares of electricity from the solar plant assure the best Well-To-Wheel indexes. Abstract: The transition to a hydrogen-based mobility requires the development of an infrastructure that must be able to satisfy the hydrogen demand. In the short and medium term, the lack of the hydrogen distribution infrastructure can be overcome through the on-site hydrogen production. However, the costs of the plants for hydrogen production, storage and distribution are currently too high and, therefore, the levelized cost of hydrogen is high above all if it is produced by renewable sources. To reduce this cost and to sustain the economic profitability of the on-site hydrogen production and distribution plants, a strong policy support and investments are required. This paper is focused on the evaluation of an incentive strategy that can assure the economic sustainability of on-site hydrogen refueling stations powered by a grid-connected solar plant. The strategy is based on the economic valorization of the carbon dioxide equivalent emissions that are avoided by adopting the proposed hydrogen pathway in comparison to the gasoline one that represents the reference for the current European powertrain technologies and trends. These carbon dioxide equivalent emissions have been estimated by applying the Well-To-Wheel analysis and the Life Cycle Cost analysis has been used to estimate the economic incentive to be paid to the avoided emission by fixing the discounted pay-back period and the current hydrogen selling price. The WTW analysis results have shown that the annual avoided equivalent emissions of the hydrogen pathway are equal to 320 tons and the corresponding economic incentives are 65.72 €/tCO2eq and 327.49 €/tCO2eq, by considering the Discounted Pay Back Periods of 10 and 8 years, respectively. Moreover, these incentives allow to achieve the Levelized Cost of Hydrogen and the Profitability Index equal to 9.02 €/kg and 1.75 (10 years) and 7.86 €/kg and 2.12 (8 years), respectively. In conclusion, the proposed incentive strategy is a suitable option to support the on-site HRS powered by grid-connected solar plants which are a promising solution for a sustainable mobility.